2016
DOI: 10.1111/all.12926
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine polarizes dendritic cells toward a Th2-promoting profile

Abstract: Our observations suggest that ACh polarizes DC toward a Th2-promoting profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 34 publications
5
34
0
4
Order By: Relevance
“…Nevertheless, in our current system, the net effect of over-expressing nematode AChE during systemic infection of mice with our vehicle is polarisation to a Th1 environment and skewing of macrophages to an M1 phenotype. Other recent published work is consistent with this observation, as cholinergic stimulation of dendritic cells promotes production of IL-4, IL-5 and IL-13 in the course of a mixed lymphocyte reaction [36]. …”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, in our current system, the net effect of over-expressing nematode AChE during systemic infection of mice with our vehicle is polarisation to a Th1 environment and skewing of macrophages to an M1 phenotype. Other recent published work is consistent with this observation, as cholinergic stimulation of dendritic cells promotes production of IL-4, IL-5 and IL-13 in the course of a mixed lymphocyte reaction [36]. …”
Section: Discussionsupporting
confidence: 87%
“…Myeloid/classic DC, plasmacytoid DC, monocyte-related DC, and Langerhans cell subtypes exert divergent biological effects as antigen presenting cells, including differential capacity for cross presentation, 24 cytokine production, and polarization toward Th1, Th2, Th17, or regulatory T cell (Treg) immunophenotypes under the influence of various microbiological and biochemical stimuli 25, 26, 27, 28. Each of these alternative DC subtypes, including Langerhans cells,29, 30, 31 DCs derived from CD34-positive umbilical cord blood progenitor cells,32, 33, 34, 35 and plasmacytoid DCs36, 37, 38, 39 have been explored for use in DC vaccine development in different solid and hematologic malignancies.…”
Section: Main Textmentioning
confidence: 99%
“…However, the mechanisms underlying the effects of parasympathetic nerves on immune cells in patients with AR are not clear. Although increasing evidence indicates the importance of parasympathetic nerves in the immune function of patients with other systematic diseases, studies of neuroimmune regulation in the field of AR have rarely been reported , , . ‐ In the present study, by establishing an in‐vitro neuroimmune coculture model of D‐U87 neurons and CD4 + T cells, we observed that cholinergic neuron‐like D‐U87 cells promoted the polarization of CD4 + T cells from patients with AR toward Th2 cells, and inhibition of the cholinergic activity of D‐U87 cells by IB decreased the preferential Th2 polarization by modulating Akt signaling.…”
Section: Discussionmentioning
confidence: 47%
“…The components of the cholinergic system, including acetylcholine (ACh), muscarinic and nicotinic receptors, acetylcholinesterase, and choline acetyltransferase, were found to be expressed by T and B cells . Treatment of dendritic cells with ACh stimulated expression of the Th2‐promoter OX40L and the synthesis of interleukin (IL)‐4, IL‐5, and IL‐13 by T cells . ACh induced polarization of naive CD4 + T cells toward the Th1, Th2, and Th17 lineages by acting on cholinergic receptors .…”
mentioning
confidence: 99%